Analisis Kecerdasan Emosional Pada Anak Usia 5-6 Tahun di TK Al-Jami’atul Washliyah Sungai Majo Kecamatan Kubu Babussalam Kabupaten Rokan Hilir - Tuti Lestari; Nurlita Nurlita; Defni Satria (Departement of Mathematics Education, 2023)
Emotional intelligence is a child’s ability to recognize, process, and control emotions so that children are able to respond positivelyto any condition that stimulates the emergence of emotions such as self-awareness, silf-regulation, motivation, recognizing other people’s emotions or empathy, and social skills. The purpose of this study was to determine emotiona intelligence in children aged 5-6 years at Al-Jami’atul Washliyah kindergarden Sungai Majo, Kubu Babussalam Dictrict, Rokan Hilir Regency. The type of research used is quantitativ descriptiv recearch. The data analysis technique used in this study is using statistical data. The results showed that emotiona intelligence in children aged 5-6 years at Al-Jami’atul Washliyah kindergarden Sungai Majo, Kubu Babussalam Dictrict, Rokan Hilir Regency was included in the good category, with a parcentage of 76,88%. This means that self-awareness, silf-regulation, motivation, recognizing other people’s emotions or empathy, and social skills in children are well developed.